CONDUCT DISORDER AND ITS CONSEQUENCES IN PHYSICAL EDUCATION CLASSES IN SCHOOL, AND SOCIAL INCLUSION (Fiep Bulletin - online, 2014)
This study aimed to verify the Conduct disorder characterized by the presence of a persistent or aggressive behavior Dissocial students who attend physical education classes by the teachers, as well as behavior within classrooms associated with a significant change and global relationships with other children. The study is descriptive and is based on motor characteristics and psychic children have, raising behavioral aspects presented in the same school in the city of Curitiba Parana State. The population comprised of 60 teachers chosen. The work was characterized as descriptive research, with the use of questionnaires to teachers, with a total of ten (10) closed and open questions to investigate aggressive behavior of the student in school.
Keywords: Conduct disorder; Physical Education; School; Social Inclusion.